"Here for the Residents": A Case Study of Cultural Competence of Personal Support Workers in a Long-Term Care Home. (March 2015) - Tayab, Aysha; Narushima, Miya
Purpose: This study explores the perception of cultural competence of personal support workers (PSWs) in a long-term care (LTC) home in Ontario. As Canada's demography becomes older and more diverse, LTC homes will increasingly accommodate residents from various cultural backgrounds. However, few studies have examined cultural competence among PSWs in the LTC home setting.Design: The study employed a qualitative case study approach. Data collection and analysis were conducted in three phases: document analysis of organizational policies, a key informant interview with the Director of Care, and two focus groups with PSWs.Results: Our findings illuminated the PSWs' broad definition of culture, the process of developing cultural competence and its strong connections to person-centered care, and the organizational factors that facilitate or hinder PSWs' cultural competence.Implications: The ambiguous perception of cultural competence reported by PSWs suggests the need for more education and further research on this topic.